Implementation of objective activity monitoring to supplement the interpretation of ambulatory esophageal PH investigations. Issue 3 (27th January 2015) - Kwasnicki, R. M.; Ley Greaves, R.; Ali, R.; Gummett, P. A.; Yang, G. Z.; Darzi, A.; Hoare, J.
Summary: Conventional catheter‐based systems used for ambulatory esophageal pH monitoring have been reported to affect patient behavior. As physical activity has been associated with gastroesophageal reflux disease (GERD), there is a risk that abnormal behavior will degrade the value of this diagnostic investigation and consequent management strategies. The aim of this study was to quantify the effect of conventional pH monitoring on behavior and to investigate the temporal association between activity and reflux. A total of 20 patients listed for 24 hours pH monitoring underwent activity monitoring using a lightweight ear‐worn accelerometer (e‐AR sensor, Imperial College London) 2 days prior to, and during their investigation. PH was measured and recorded using a conventional nasogastric catheter and waist‐worn receiver. Daily activity levels, including subject‐specific activity intensity quartiles, were calculated and compared. Physical activity was added to the standard pH output to supplement interpretation. Average patient activity levels decreased by 26.5% during pH monitoring (range −4.5 to 51.0%, P = 0.036). High‐intensity activity decreased by 24.4% (range −4.0 to 75.6%, P = 0.036), and restful activity increased on average by 34% although this failed to reach statistical significance (−24.0 to 289.2%, P = 0.161). Some patients exhibited consistent associations between bouts of activity and acidic episodes. The results of this study support the previously reported reduction in activity during ambulatory esophageal pH monitoring, with the added reliability of objective data. In the absence of more pervasive pH monitoring systems (e.g. wireless), quantifying activity changes in the setting of activity‐induced reflux might guide the physicians' interpretation of patient DeMeester scores resulting in more appropriate management of GERD.